“Al mejor servicio del rey”. Indígenas realistas en la contrarrevolución quiteña, 1809-1814 (Estudios) - Sevilla Naranjo, Rosita Alexandra (2016)
This study explores the motivations and the ways in which indigenous communities and their chiefs articulated themselves to the Quito counterrevolution, between 1809 and 1814. It seeks to highlight and problematize relations between the local elite and the indigenous population during the revolutionary period, turning away from teleological readings that exalt the construction of the nation. From the analysis of specific cases there is evidence that loyalty to the king, as a result of a response to “juntismo”, of the early 19th Century, was a political and practical option for the indigenous population of the Audiencia de Quito.